Melanoma-reactive T cells in the bone marrow of melanoma patients: association with disease stage and disease duration - Müller-Berghaus, Jan; Ugurel, Selma; Umansky, Viktor; Schirrmacher, Volker; Beckhove, Philipp; Schadendorf, Dirk (Cancer research, 2006)
Using IFN-γ enzyme-linked immunospot, we investigated reactivity of T cells from bone marrow and peripheral blood to melanoma lysate-pulsed autologous dendritic cells in 40 melanoma patients. Melanoma-reactive T cells were present in the bone marrow of seven patients and in peripheral blood of four patients. In the bone marrow, melanoma-reactive T cells were present in 6 of 21 stage IV patients and in 1 of 10 stage III patients, whereas none were detected in stage I to II patients (0 of 9). The occurrence of tumor-reactive bone marrow T cells in melanoma patients was associated with advanced disease stage, disease duration and tumor load, and independent of treatment. These findings provide new insights into the generation of T-cell responses in melanoma patients.